(untitled) (International Journal of Language, Literacy and Translation, 2025)
The difficulty of translating classical Chinese poetry into English is mainly related to the background differences between Chinese and Western cultures. In literary translation, especially poetry, translating thoughts and emotions in classical Chinese that preserve the artistic conception of the source text could be one of the main challenges that literary translators face. In this study, Yan Fu's translation theory was employed to analyze the translations of classical Chinese poetry and identify the dominant principle in translating classical Chinese poetry to English. Ten classical Chinese poems were selected purposefully to describe the translatability features of the classical Chinese poems into English qualitatively. The artistic conception and polysemes were analyzed and exemplified to explore how they were portrayed. Descriptions of how footnotes were used in creating the artistic conception in the English translation of the selected classical Chinese poems were provided. The findings indicated that the use of polysemy and footnotes can help to maintain the artistic conception in the English translations of classical Chinese poetry. Application of Yan Fu's translation theory may enhance the quality of translated classical Chinese.